VD_FINDINFO MP / 2014 / 3 vom 9. April 2014 - VD Tribunal cantonal (2014)
CONCURRENCE DÉLOYALE, PROTECTION DES MARQUES, RAISON DE COMMERCE | 944 CO, 956 al. 2 CO, 2 LCD, 3 al. 1 let. d LCD, 13 al. 2 LPM, 261 CPC (CH), 262 CPC (CH)